Assembling performance measurement through engagement - Martinez, Daniel E.; Cooper, David J. (Accounting, Organizations and Society, 2019)
Taking inspiration from studies of performance measurement systems and an understanding of the materiality of inscription devices, we examine how a loose network of funding agencies and non-governmental organizations (NGOs) assemble a performance and management system out of accountability requirements. As part of the funding process, international development agencies provide NGOs with a series of planning and project reporting requirements such as budgets, operational plans, and strategic plans. Our study focusses on how these requirements' visual features enable users to perform the calculative properties of the performance system, as a whole. Specifically, we learn how a planning and performance measurement device such as the logical framework accumulates financial, chronological, and strategic modes of ordering through a patchwork of interventions to address perceived and unexpected shortcomings. We find that it is not just a matter of adding patches to improve, but also about fostering engagement with the changing assemblage of devices and development concerns. Our study is based on field research in Guatemala and El Salvador and contributes to our understanding of how governing bodies intervene in the constitution of a calculative workspace. By analysing an accounting system's relation with other devices and their modes of ordering and calculating, we learn how a workspace for providing accounts is assembled and engaged with for actors to perform a mode of governing.